Learning Media Based on Google Sites to Improve Critical Thinking in Senior High School Students - Anik Wahyunigtyas; Triwahyuni, Eges (Jurnal Pedagogi dan Pembelajaran, 2025)
To foster critical thinking skills, media that is interesting, enjoyable, and appropriate to students' needs is required. Twenty-first century education demands the integration of technology in the teaching and learning process to create contextual and interesting learning. This study aims to develop Google Sites learning media to enhance the critical thinking skills of Grade XI high school students in Biology, particularly in the subject of cell structure. This research is a development study based on the ADDIE development model. The research data sources are validity experts and 11th-grade high school students. Data collection procedures use interviews, validation, observation, questionnaires, and tests. The analysis methods used in this study are qualitative and quantitative. Qualitative descriptive data analysis was obtained from critiques and feedback from the media and material validation team. Quantitative data was obtained from the results of percentage calculations using a Likert scale and students' pretest-posttest scores, analysed using the N-Gain test. The validation score by media experts reached 95%, while the validation score by material experts reached 100%. Both fall within the highly acceptable criteria. Student responses to the practicality of the media showed a score of 85% (practical). There was a significant increase in students' critical thinking skills with an average N-Gain score of 0.40 (moderate). It can be concluded that the development of Google Sites learning media is highly acceptable, practical, and effective in enhancing students' critical thinking skills.